Participatory analysis of groundnut (Arachis hypogaea L.) cropping system and production constraints in Burkina Faso - Boubacar Sinare; Amos Miningou; Baloua Nebié; John Eleblu; Ofori Kwadwo; Appolinaire Traoré; Bertin Zagre; Haile Desmae (Journal of Ethnobiology and Ethnomedicine, 2021)
Abstract Background Groundnut is one of the major legume crops grown as food and cash crop across the different agroecological zones of Burkina Faso. It is ranked the 2nd important legume crop for household food, nutrition, and income generation for both rural and urban zones, contributing significantly to food supply and economy of the country. Despite its importance and breeding efforts to develop improved varieties, groundnut productivity remains low. Assessing and describing the present groundnut cropping system and production constraints as well as gender dynamics in the main production areas will help in defining the groundnut breeding priorities. Methods A participatory rural appraisal study was conducted in three groundnut production regions (central-eastern, central-northern, and central-western). In each region, 4 villages were selected with a total of 124 farmers interviewed to collect data on socio-demographics, farming systems, cropping practices, and production constraints. Data analysis was carried out for qualitative and quantitative variables using STATA 14. Analysis of variance was conducted across regions and gender, and also between and within regions. Kendall’s coefficients were determined for qualitative variables across regions for the constraints using the pairwise rank. Pearson’s correlation was carried out to assess the relationship between variables, and the chi-square test was used to assess the difference in farmer preferences. Results The study revealed a cropping system of groundnut in an environment largely affected by climate change and in a subsistence and extensive agriculture. There is a variation in the groundnut cropping system across the regions. Gender plays a key role in the production of the groundnut, and 48.39% of women are engaged in groundnut cropping with less access to land and production resources. A yield gap between men and women was observed with men achieving more yield than women. There was a strong correlation between the use of improved varieties and technical assistance. A strong correlation was observed between farm size and production, and farm size and sex denoting an extensive production. Production constraints, although similar, were perceived and ranked differently between regions. The lack of improved varieties, absence of agricultural credit, lack of production tools, the high price of seeds, the high price of fertilizer, drought, and disease are some of the important constraints affecting groundnut productivity. Conclusion This study provides a recent view of groundnut cropping, allowing a good understanding of the farmers’ situation. The result will contribute to the refining of breeding priorities and guide further activities in groundnut breeding in Burkina Faso.